2017
DOI: 10.1021/acsinfecdis.7b00052
|View full text |Cite
|
Sign up to set email alerts
|

Optimized Fluorescence Complementation Platform for Visualizing Salmonella Effector Proteins Reveals Distinctly Different Intracellular Niches in Different Cell Types

Abstract: The bacterial pathogen Salmonella uses sophisticated type III secretion systems (T3SS) to translocate and deliver bacterial effector proteins into host cells to establish infection. Monitoring these important virulence determinants in the context of live infections is a key step in defining the dynamic interface between the host and pathogen. Here, we provide a modular labeling platform based on fluorescence complementation with split-GFP that permits facile tagging of new Salmonella effector proteins. We demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(36 citation statements)
references
References 48 publications
(140 reference statements)
0
36
0
Order By: Relevance
“…Poorly expressed or diffusely localised effectors present a greater challenge for microscopic tracking, particularly in real time where photobleaching is a concern. The application of tandem repeat fluorescent tags is sometimes not sufficient to overcome issues with low signal from such effectors (Park et al, ; Young et al, ). Multimerisation of tags comes at the cost of increased propensity for aggregate formation and an increased risk of interfering with functionality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Poorly expressed or diffusely localised effectors present a greater challenge for microscopic tracking, particularly in real time where photobleaching is a concern. The application of tandem repeat fluorescent tags is sometimes not sufficient to overcome issues with low signal from such effectors (Park et al, ; Young et al, ). Multimerisation of tags comes at the cost of increased propensity for aggregate formation and an increased risk of interfering with functionality.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a recent study demonstrated that 3×GFP 11 labelling of the Salmonella SPI2 effector proteins SseF, SseG, and SlrP resulted in higher fluorescence intensity; however, due to low levels of expression from their endogenous promoters, an experimental set‐up involving plasmid‐based expression driven by the stronger steA promoter was favoured over chromosomal tagging. The resultant signal amplification allowed for real‐time identification of differential effector localisation in infected primary macrophages and HeLa cells (Young, Minson, McQuate, & Palmer, ). A tripartite split‐GFP labelling method has also been developed to allow the study of protein–protein interactions and to reduce background levels due to aggregation and spontaneous reassociation that are sometimes observed with the GFP 1–10 /GFP 11 system.…”
Section: Effector‐tagging Methodologiesmentioning
confidence: 99%
“…Effectors tagged with a fluorescent peptide allow following the secretion process from the intracellular bacteria by the loss of fluorescence. Another approach consists on an adaptation of the split‐green fluorescent protein (GFP) assay, fusing the FP11 GFP domain to the effector and expressing the rest of the GFP protein (FP1‐10) in the host cell (Batan et al, ; Young, Minson, McQuate, & Palmer, ).…”
Section: Effector‐mediated Subversion Of Host Cellsmentioning
confidence: 99%
“…Live-fluorescence-microscopy approaches are ideal to dissect dynamics of bacterial infections on a single-cell level. We and others previously developed live fluorescence tools to visualize and quantify effector proteins secreted from different Gram-negative pathogens in infection, including Salmonella, Shigella, and Escherichia coli (33)(34)(35)(36)(37)(38)(39)(40). The effector proteins labeled by different fluorescent tags in these studies are secreted by the type III secretion system (41), a well-studied and common protein secretion pathway across the inner and outer membrane in Gram-negative bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…The effector proteins labeled by different fluorescent tags in these studies are secreted by the type III secretion system (41), a well-studied and common protein secretion pathway across the inner and outer membrane in Gram-negative bacteria. A particularly powerful tool is the split-green fluorescent protein (GFP) system, in which the last b-strand of GFP (GFP11, 16 amino acids) is genetically fused to the protein of interest via a short and flexible linker (34,35) (see also Fig. 1 a).…”
Section: Introductionmentioning
confidence: 99%